CS-SA / OPL / EGCG composite hydrogel and preparation method thereof

CS-SA/OPL/EGCG composite hydrogels with antibacterial and wound healing were prepared by adding epigallocatecin gallate to sialic acid modified chitosan and oxidized pluland glycan hydrogels to a sialic acid modified chitosan and oxidized pluland glycan hydrogels. , solves the problems of infection and reactive oxygen damage during wound healing, and achieves significant antibacterial and cell migration effects.

CN119215223APending Publication Date: 2024-12-31XINYANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364030.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Healing is hindered by persistent infection and reactive oxygen damaging new blood vessel formation during wound healing, leading to an increased risk of chronic wounds and complications, and a multifunctional dressing with antibacterial and promotes wound healing is needed.

Method used

Develop a CS-SA/OPL/EGCG composite hydrogel that modifies the Schiff base reaction between sialic acid and oxidized prolantosan, and adds epigallocatecin gallic acid to it Ester, hydrogels with good water absorption, adhesion and antibacterial properties were prepared.

Benefits of technology

The hydrogel significantly improves the antibacterial and antioxidant activity against E. coli and Staphylococcus aureus, enhances cell viability and migration capabilities, and demonstrates its potential in wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215223A_ABST
    Figure CN119215223A_ABST
Patent Text Reader

Abstract

The invention discloses CS-SA (sialic acid modified chitosan) / OPL (oxidized pulullan polysaccharide) / EGCG (epigallocatechin gallate) composite hydrogel. The composite hydrogel is prepared from CS-SA (sialic acid modified chitosan), OPL (oxidized pulullan polysaccharide) and EGCG. Meanwhile, the invention further discloses a preparation method of the hydrogel, the multifunctional CS-SA / OPL hydrogel is developed through a Schiff base reaction between sialic acid coupled chitosan and oxidized pullulan chitosan, and EGCG is added in situ. The prepared hydrogel has a porous microstructure, relatively high water absorption capacity and good self-healing performance and adhesion performance. EGCG is added into the prepared hydrogel, so that the antibacterial activity, the antioxidant activity and the cell compatibility of the hydrogel can be promoted. The invention provides a new strategy for the preparation of the multifunctional hydrogel dressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a hydrogel medical auxiliary material, and in particular to a CS-SA / OPL / EGCG composite hydrogel and a preparation method thereof. Background Art

[0002] Wound healing is a complex process, usually, there are four overlapping stages: hemostasis, inflammation, proliferation and remodeling, however, when it comes to the scene of healing process is interrupted by external factors, such as persistent infection or intrinsic wounds that cannot heal, the wound may develop into a chronic wound, which is associated with persistent infection and bacterial invasion, and reactive oxygen species (ROS) impair the formation of new blood vessels, which further hinders the wound healing process, and effective interventions and treatment strategies must be used to meet clinical challenges. This increases the risk of wound infection, which may lead to ulcers, necrosis and even life-threatening complications.

[0003] Therefore, it is necessary to design and synthesize multifunctional wound dressings with antibacterial and wound healing properties. Summary of the invention

[0004] The object of the present invention is to provide a CS-SA / OPL / EGCG composite hydrogel, and providing a preparation method thereof is the second invention object of the present invention.

[0005] To achieve the above-mentioned purpose, the present invention is implemented by the following technical solutions:

[0006] A CS-SA / OPL / EGCG composite hydrogel is prepared from sialic acid-modified chitosan CS-SA, oxidized pullulan OPL and epigallocatechin gallate EGCG.

[0007] The preparation method of the CS-SA / OPL / EGCG composite hydrogel comprises the following steps:

[0008] 1) First, 2.0-2.4 g of chitosan CS was dispersed in 250 mL of deionized water for 3-5 min, and 3-5 mL of glacial acetic acid was added and stirred to obtain a CS solution; then, 1.6-1.8 g of N-acetylneuraminic acid, 0.8-1.0 g of NHS and 1.4-1.6 g of EDC were added to 50 mL of MES buffer to obtain a SA solution, and then the CS solution and the SA solution were mixed at room temperature for 22-24 h, and then dialyzed and freeze-dried to obtain sialic acid-modified chitosan CS-SA;

[0009] 2) Dissolve 12.0-14.0 g of pullulan polysaccharide PL in 250 mL of deionized water, add 10.0-12.0 g of sodium periodate in a dark environment, stir at room temperature for 22-24 hours, dialyze, and freeze-dry to obtain oxidized pullulan polysaccharide OPL;

[0010] 3) dispersing the sialic acid-modified chitosan CS-SA obtained in step 1) in water to prepare a CS-SA aqueous solution; dissolving the oxidized pullulan OPL obtained in step 2) in water, and then adding epigallocatechin gallate EGCG to mix to obtain an OPL / EGCG aqueous solution; and then mixing the CS-SA aqueous solution and the OPL / EGCG aqueous solution at room temperature to obtain a CS-SA / OPL / EGCG composite hydrogel.

[0011] Preferably, in step 3), the CS-SA aqueous solution and the OPL / EGCG aqueous solution are mixed in a volume ratio of 1:1.

[0012] Preferably, in the dialysis and freeze-drying of step 1), deionized water is used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag is 8-14 kDa, and the freeze-drying temperature is -80°C; in the dialysis and freeze-drying of step 2), deionized water is used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag is 3 kDa, and the freeze-drying temperature is -80°C.

[0013] Preferably, in step 3), in the CS-SA aqueous solution, the ratio of CS-SA to water is 0.24 g:8 mL; in the OPL / EGCG aqueous solution, the ratio of OPL, EGCG to water is 0.24 g:(0.12 g to 0.24 g):8 mL.

[0014] Compared with the prior art, the technical effects of the present invention are:

[0015] The present invention first disperses epigallocatechin gallate in oxidized pullulan polysaccharide, and then in situ incorporates epigallocatechin gallate into sialic acid-modified chitosan / oxidized pullulan polysaccharide to prepare CS-SA / OPL / EGCG composite hydrogel, which not only has good water absorption capacity (more than 37g / g), but also has good self-healing performance and adhesion performance. After adding epigallocatechin gallate, its antibacterial effect and antioxidant activity on Escherichia coli and Staphylococcus aureus are significantly improved. In vitro L929 cell experiments confirm that the addition of epigallocatechin gallate can also significantly improve cell viability and cell migration, further indicating that the hydrogel of the present invention has particularly good potential in wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1FT-IR spectra, a: CS and CS-SA; b: PL and OPL; c: composite hydrogel;

[0017] Figure 2 Rheological properties of CS-SA / OPL / EGCG 0% composite hydrogels obtained in Comparative Examples 1-3;

[0018] Figure 3 Microscopic morphologies of hydrogels with different EGCG contents obtained in Examples 1, 4 and Comparative Example 1;

[0019] Figure 4 Performance test of CS-SA / OPL / EGCG 0% composite hydrogel, a: water absorption and swelling performance; b: compression performance; c: degradation performance;

[0020] Figure 5 Adhesion properties of CS-SA / OPL / EGCG composite hydrogels of Examples 1, 4 and Comparative Example 1;

[0021] Figure 6 Antibacterial properties of the CS-SA / OPL / EGCG composite hydrogels of Examples 1, 4 and Comparative Example 1;

[0022] Figure 7 CCK-8 data of CS-SA / OPL / EGCG composite hydrogels of Examples 1, 4 and Comparative Example 1 co-cultured with L929 cells for 24 h;

[0023] Figure 8 The cell migration promoting performance of the CS-SA / OPL / EGCG composite hydrogels of Examples 1, 4 and Comparative Example 1 when co-cultured with L929 cells. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0025] In each embodiment of the present invention, chitosan (deacetylation degree ≥ 95%, viscosity 1000-2000 cP), pullulan (molecular weight 15-20 kD), N-acetylneuraminic acid (sialic acid, 98%), sodium periodate (NaIO4, 99.5%), N-hydroxysuccinimide (NHS, 98%), 1-ethyl 3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC, 98.5%) and 2,2′-azidobis(3-ethylbenzothiazoline-6-sulfonic acid) disalt (ABTS, 98%), 2-(N-molybdenum)ethanolsulfonic acid (MES, 99%), glacial acetic acid (99.5%), epigallocatechin gallate (epigallocatechin gallate, 98%) and potassium persulfate (99%) are purchased from the market.

[0026] The room temperature described in this embodiment and other embodiments is understood to be 25°C. In other embodiments of the present invention, the present invention can also select any value between 20-30°C for the room temperature to achieve the effect of the present invention.

[0027] Example 1

[0028] A CS-SA / OPL / EGCG composite hydrogel is prepared from sialic acid-modified chitosan CS-SA, oxidized pullulan OPL and epigallocatechin gallate EGCG.

[0029] The preparation method comprises the following steps:

[0030] 1) First, 2.0 g of CS was dispersed in 250 mL of deionized water for 3 min, and 3 mL of glacial acetic acid was added and stirred to obtain a CS solution; then, 1.6 g of N-acetylneuraminic acid, 0.8 g of NHS and 1.4 g of EDC were dissolved in 50 mL of MES buffer and stirred for 20 min to obtain a SA solution, and then the CS solution and SA solution were mixed and reacted at room temperature for 24 h, and then dialyzed and freeze-dried to obtain sialic acid-modified chitosan CS-SA; in the dialysis and freeze-drying of step 1), deionized water was used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag was 8-14 kDa, and the freeze-drying temperature was -80°C;

[0031] 2) Dissolve 12.0 g of pullulan polysaccharide PL in 250 mL of deionized water, add 10.0 g of sodium periodate in a dark environment, stir at room temperature for 24 hours, dialyze and freeze-dry to obtain oxidized pullulan polysaccharide OPL; in the dialysis and freeze-drying of step 2), deionized water is used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag is 3 kDa, and the freeze-drying temperature is -80°C.

[0032] 3) Dispersing the sialic acid-modified chitosan CS-SA obtained in step 1) in water to prepare a CS-SA aqueous solution; dissolving the oxidized pullulan polysaccharide OPL obtained in step 2) in water, and then adding epigallocatechin gallate EGCG to mix to obtain an OPL / EGCG aqueous solution; then mixing the CS-SA aqueous solution and the OPL / EGCG aqueous solution at a volume ratio of 1:1 at room temperature to obtain a CS-SA / OPL / EGCG composite hydrogel. In step 3), in the CS-SA aqueous solution, the amounts of CS-SA and water are 0.24 g and 8 mL, respectively; in the OPL / EGCG aqueous solution, the amounts of OPL, EGCG and water are 0.24 g, 0.12 g, and 8 mL, respectively.

[0033] The CS-SA / OPL / EGCG composite hydrogel obtained in this example is recorded as CS-SA / OPL / EGCG1.5%.

[0034] Example 2

[0035] The CS-SA / OPL / EGCG composite hydrogel and its preparation method in this embodiment are the same as those in Example 1, except that:

[0036] In step 1), 2.4 g CS was first dispersed in 250 mL deionized water for 5 min, and 5 mL glacial acetic acid was added and stirred to obtain a CS solution; 1.8 g N-acetylneuraminic acid, 1.0 g NHS and 1.6 g EDC were added to 50 mL MES buffer to obtain a SA solution, and then the CS solution and SA solution were mixed and reacted for 22 to 24 h, and then dialyzed and freeze-dried to obtain sialic acid-modified chitosan CS-SA;

[0037] In step 2), 14.0 g of pullulan polysaccharide PL is dissolved in 250 mL of deionized water, 12.0 g of sodium periodate is added in a dark environment, and the mixture is stirred at room temperature for 22 to 24 hours, and then dialyzed and freeze-dried to obtain oxidized pullulan polysaccharide OPL.

[0038] Example 3

[0039] The CS-SA / OPL / EGCG composite hydrogel and its preparation method in this embodiment are the same as those in Example 1, except that:

[0040] In step 1), 2.2 g CS was first dispersed in 250 mL deionized water for 4 min, and 4 mL glacial acetic acid was added and stirred to obtain a CS solution; 1.7 g N-acetylneuraminic acid, 0.9 g NHS and 1.5 g EDC were added to 50 mL MES buffer to obtain a SA solution, and then the CS solution and SA solution were mixed and reacted for 23 h, and then dialyzed and freeze-dried to obtain sialic acid-modified chitosan CS-SA;

[0041] In step 2), 13.0 g of pullulan polysaccharide PL was dissolved in 250 mL of deionized water, 11.0 g of sodium periodate was added in a dark environment, and the mixture was stirred at room temperature for 23 h, and then dialyzed and freeze-dried to obtain oxidized pullulan polysaccharide OPL.

[0042] Example 4

[0043] The CS-SA / OPL / EGCG composite hydrogel and its preparation method in this embodiment are the same as those in Example 1, except that in step 3), the usage ratio of OPL, EGCG and water is 0.24 g:0.24 g:8 mL, and the obtained composite hydrogel is recorded as CS-SA / OPL / EGCG 3%.

[0044] Comparative Example 1

[0045] The composite hydrogel and preparation method of this comparative example are the same as those of Example 1, except that in step 3), epigallocatechin gallate EGCG is not added. The obtained composite hydrogel is recorded as CS-SA / OPL / EGCG0%11.

[0046] Comparative Example 2

[0047] The composite hydrogel and preparation method thereof of this comparative example are the same as those of Example 1, except that in step 3), epigallocatechin gallate EGCG is not added, and the volume ratio of CS-SA solution to OPL aqueous solution is 1:3. The obtained composite hydrogel is recorded as CS-SA / OPL / EGCG0%13.

[0048] Comparative Example 3

[0049] The composite hydrogel and preparation method thereof of this comparative example are the same as those of Example 1, except that in step 3), epigallocatechin gallate EGCG is not added, and the volume ratio of CS-SA solution to OPL aqueous solution is 3:1. The obtained composite hydrogel is recorded as CS-SA / OPL / EGCG0%31.

[0050] Structural confirmation, performance testing and effect experiments

[0051] 1. Structure confirmation

[0052] Taking the CS-SA and OPL obtained in step 1) and step 2) of Example 1 as examples, FT-IR test was performed. At the same time, taking Example 1 and Comparative Example 1 of Example 4 as examples, FT-IR test was performed on the obtained hydrogels with different EGCG contents. The results are shown in Figure 1 shown.

[0053] In the FT-IR spectra of CS and CS-SA ( Figure 1 a) at 2913 and 1583 cm-1 New peaks appeared at 1618 cm-1, which is due to the CH stretching of the methyl group and the stretching of -CH3, which is mainly due to the grafting of SA onto CS. -1 The angular deformation at 100° is reduced, which is due to the transplantation of SA onto the primary amines of CS. Figure 1 b), the peak is at 1618 cm -1 The 1648 cm -1 The peak value appears at Figure 1 c) It can be determined as a typical -CH=N, mainly based on the Schiff base reaction between CS-SA and OPL, which also confirms the formation of hydrogel.

[0054] 2. Rheological properties test of hydrogel

[0055] The rheological properties of the CS-SA / OPL / EGCG 0% composite hydrogels obtained in Comparative Examples 1 to 3 were evaluated using a rheometer. The results are shown in Figure 2 shown.

[0056] Figure 2 In the experiment, the storage modulus (G') of all hydrogels was significantly greater than the loss modulus (G') in both frequency and time, indicating that the CS-SA / OPL of the present invention has typical hydrogel behavior. In addition, compared with the other two samples, the G' of the hydrogel sample using the CS-SA solution:OPL solution ratio of 1:1 is higher, indicating that the hydrogel under this ratio has better mechanical strength. Therefore, the present invention selects the CS-SA / OPL solution ratio of 1:1 as the main experimental group.

[0057] 3. Scanning electron microscope test

[0058] The hydrogels with different EGCG contents obtained in Example 1, Example 4 and Comparative Example 1 were observed by scanning electron microscopy. Figure 3 shown.

[0059] According to the results of scanning electron microscopy images, the addition of EGCG had no significant effect on the pore structure, and all composite hydrogels showed an interconnected porous structure, which provided a basis for fluid absorption, nutrient exchange and cell migration.

[0060] 4. Hydrogel performance test

[0061] The water absorption performance, mechanical properties and degradation performance of the hydrogels with different EGCG contents obtained in Example 1, Example 4 and Comparative Example 1 were tested. The results are shown in Figure 4 shown.

[0062] from Figure 4The results of a show that the addition of EGCG has little effect on the water absorption performance of the composite hydrogel, which is consistent with the results of the microscopic morphology test. The composite hydrogel was further subjected to compression testing. Figure 4 As shown in Figure b, the results show that the addition of EGCG can effectively enhance the mechanical properties of the hydrogel, while excessive addition of EGCG will also affect the enhancement effect. The degradation properties of the composite hydrogel before and after the addition of EGCG were tested. Figure 4 From the results of c, it can be seen that the addition of EGCG has little effect on the degradation performance of the composite hydrogel.

[0063] 5. Analysis of adhesion properties of hydrogel

[0064] The sample adhesion test was carried out using Example 1, Example 4 and Comparative Example 1 of the present invention as examples. The results are as follows: Figure 5 As shown in the figure, all composite hydrogel samples have good adhesion properties, and the bonding materials include glass, rubber, plastic, metal and skin. The addition of EGCG has a certain weakening effect on the bonding performance, but has little effect on its bonding performance.

[0065] 6. Antimicrobial activity

[0066] The antibacterial activity of CS-SA / OPL / EGCG composite hydrogel was studied using typical Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. Figure 6 ). After incubation of the hydrogel with bacteria for 6 hours, the sialic acid-modified chitosan / oxidized pullulan hydrogel without epigallocatechin gallate showed a significant inhibition zone. With the addition of epigallocatechin gallate, the hydrogel showed a larger inhibition zone. According to the statistical diameter of the inhibition zone, the antibacterial activity of the hydrogel against Staphylococcus aureus and Escherichia coli increased with the increase of epigallocatechin gallate content.

[0067] 7 Biocompatibility

[0068] The cytocompatibility of CS-SA / OPL / EGCG composite hydrogels was investigated by co-culturing L929 cells with the hydrogel extracts, as an important factor for cytocompatibility in wound dressing applications. The growth of metabolically active cells was quantitatively evaluated using the CCK-8 assay ( Figure 7 ). The cell viability of each group of cells gradually increased, and the incorporation of EGCG can promote the growth and proliferation of L929 cells. Finally, the cell scratch method was used to evaluate the migration ability of CS-SA / OPL / EGCG composite hydrogel. The results are shown in Figure 8As shown. Compared with the control group, the CS-SA / OPL / EGCG composite hydrogels without epigallocatechin gallate and with epigallocatechin gallate showed higher cell migration ability within a few hours. With the increase of EGCG content, the CS-SA / OPL / EGCG composite hydrogel significantly improved the cell migration ability. The results of in vitro L929 cell experiments showed that the prepared CS-SA / OPL / EGCG composite hydrogel had good biocompatibility and cell migration ability, and it was possible to accelerate the closure of cell scratches.

[0069] Therefore, the present invention develops a multifunctional sialic acid-modified chitosan / oxidized pullulan polysaccharide hydrogel through the Schiff base reaction between sialic acid-coupled chitosan and oxidized pullulan chitosan, and adds epigallocatechin gallate in situ. The prepared hydrogel has a porous microstructure, high water absorption capacity, good self-healing performance and adhesion performance. Adding epigallocatechin gallate to the prepared hydrogel can promote its antibacterial activity, antioxidant activity and cell compatibility. The present invention provides a new strategy for the preparation of multifunctional hydrogel dressings.

Claims

1. A CS-SA / OPL / EGCG composite hydrogel, characterized in that: The composite hydrogel is prepared from sialic acid-modified chitosan CS-SA, oxidized pullulan OPL and epigallocatechin gallate EGCG.

2. The method for preparing the CS-SA / OPL / EGCG composite hydrogel according to claim 1, characterized in that: The following steps are involved: 1) First, 2.0-2.4 g of CS was dispersed in 250 mL of deionized water for 3-5 min, and 3-5 mL of glacial acetic acid was added and stirred to obtain a CS solution; then, 1.6-1.8 g of N-acetylneuraminic acid, 0.8-1.0 g of NHS and 1.4-1.6 g of EDC were added into 50 mL of MES buffer to obtain a SA solution, and then the CS solution and the SA solution were mixed and reacted at room temperature for 22-24 h, and then dialyzed and freeze-dried to obtain sialic acid-modified chitosan CS-SA; 2) Dissolve 12.0-14.0 g of pullulan polysaccharide PL in 250 mL of deionized water, add 10.0-12.0 g of sodium periodate in a dark environment, stir at room temperature for 22-24 hours, dialyze, and freeze-dry to obtain oxidized pullulan polysaccharide OPL; 3) dispersing the sialic acid-modified chitosan CS-SA obtained in step 1) in water to prepare a CS-SA aqueous solution; dissolving the oxidized pullulan OPL obtained in step 2) in water, and then adding epigallocatechin gallate EGCG to mix to obtain an OPL / EGCG aqueous solution; and then mixing the CS-SA aqueous solution and the OPL / EGCG aqueous solution at room temperature to obtain a CS-SA / OPL / EGCG composite hydrogel.

3. The method for preparing the CS-SA / OPL / EGCG composite hydrogel according to claim 2, characterized in that: In step 3), the CS-SA aqueous solution and the OPL / EGCG aqueous solution are mixed in a volume ratio of 1:

1.

4. The method for preparing the CS-SA / OPL / EGCG composite hydrogel according to claim 2, characterized in that: In the dialysis and freeze-drying of step 1), deionized water is used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag is 8-14 kDa, and the freeze-drying temperature is -80°C; in the dialysis and freeze-drying of step 2), deionized water is used for dialysis for 5 days, the molecular weight cutoff MWCO of the dialysis bag is 3 kDa, and the freeze-drying temperature is -80°C.

5. The method for preparing the CS-SA / OPL / EGCG composite hydrogel according to claim 2, characterized in that: In step 3), in the CS-SA aqueous solution, the ratio of CS-SA to water is 0.24 g:8 mL; in the OPL / EGCG aqueous solution, the ratio of OPL, EGCG to water is 0.24 g:(0.12 g to 0.24 g):8 mL.